Improving Low-Voltage Ride-Through Performance and Alleviating Power Fluctuation of DFIG Wind Turbine in DC Microgrid by Optimal SMES with Fault Current Limiting Function - Ngamroo, Issarachai; Karaipoom, Tanapon (My University, 2014)
The vital problems of doubly fed induction generator (DFIG) wind turbine are power fluctuation and low-voltage ride-through performance. To tackle both problems, the new circuit configuration and optimization technique of the superconducting magnetic energy storage with fault current limiting function (SMES-FCL) in a DC microgrid are presented. The SMES-FCL circuit mainly consists of two DC choppers with common superconducting coil (SC). During normal operation, the SMES-FCL acts as the SMES unit to suppress the power fluctuation of DFIG. When severe faults occur in the system, the SC is automatically connected to the system and used as the fault current limiter. Consequently, the fault current and the terminal voltage drop of DFIG can be alleviated. The energy function method is used to formulate the optimization problem of SC inductance, initial stored energy, and proportional-integral control parameters of choppers. Simulation study confirms the superior control effect of the SMES-FCL over the conventional SMES.
Keywords: Doubly fed induction generator wind turbine; energy function method; fault current limiter; optimization; superconducting magnetic energy storage